The Impact of Knowledge of Sustainable Manufacturing Practices on Purchase Intention Towards Fashion Apparel - Bajaj, Bhavna; Paul, Ann (Ushus Journal of Business Management, 2022)
Indian apparel manufacturers are promoting sustainable fashion and reducing carbon footprint. Despite these efforts, the acceptance of green apparel in India is low compared to developed countries. In the current study, the impact of sustainable manufacturing practices on consumers’ purchase intention has been investigated while controlling for consumers' knowledge of sustainable manufacturing practices (SMPs). Data from 100 respondents analyzed using bivariate regression suggests that relationship between Consumers' Environmental Impact Consciousness, Consumers' Awareness of a brand's SMPs and their Purchase Intention toward the brand is differentially impacted by Consumers' own Knowledge of Sustainable Manufacturing Practices. The results carry implications for marketers who must craft messages to raise consumers’ knowledge of sustainable practices, as well as the consumers' awareness of brands' use of SMPs.